Design and Acceptability Testing of a Medical Data Collection System Using Smart Technologies - Meurer, Mark; Rosinkranz, Haukur (My University, 2016)
The purpose of this thesis is to identify key criteria that maximizes the acceptability of a data collection and visualization system using smart devices for cancer surviving patients and their nurses. It focuses on oncology nurses and their respective pelvic region cancer surviving patients. The thesis makes use of participatory research and participatory design. Specifically, a case study on nurses and patients of Sahlgrenska universities oncology department was conducted. It was done in collaboration with EfterCancern, a collaboratory research group within Sahlgrenska’s oncology department. The data was gathered by a series of interviews and workshops with the nurses as well as a one month usability study with a patient. In addition, parts of design science research was used by creating prototypes and evaluating them with the participatory parties. The developed software includes a server backend, a web portal, and a mobile application. Smart devices including Flic buttons and FitBit armbands were used. The devices communicate with various parts of the system. The results were taken from a thematic analysis of the collected data and the associated usage data from the devices and software. The nurses major acceptability factor for the smart devices was purely in the data gathered by the said devices. In regards to the software they would be interacting with, the biggest criteria is that they must believe that the software is helping them and/or the patients. A more measurable criteria is that the software must easily supplement their work practices and be easy to learn. It also came apparent that the similarity to the nurses previously used systems largely affects the learnability and understandability. On the other hand, the patients acceptability of the collection system and smart devices mostly regarded their motivation for using the said technologies and the autonomy of the devices.
Keywords: Data- och informationsvetenskap; Computer and Information Science